Development and Evaluation of Transdermal Patches of Quetiapine fumerate for the treatment of psychosis - Akanksha Namdeo; Navneet Garud; Akanksha Garud (International Journal of Drug Delivery, 2012)
The aim of the present study was to formulate and evaluate the transdermal patches of an antipsychotic drug Quetiapine fumerate (QF) for the treatment of psychosis and schizophrenia. The transdermal patches was prepared by the solvent evaporation method using hydroxy propyl methyl cellulose (HPMC) and ethyl cellulose (EC) in five different ratios 1:0, 2:1, 1:1, 1:2, 0:1. The PEG-400 and DMSO were used as plasticizers and permeation enhancer respectively to enhance the permeability of the drug. The FTIR studies showed no evidence of incompatibility between the drug and the polymers. The prepared patches were evaluated for various parameters like thickness, weight variation, folding endurance, percentage moisture uptake, percentage moisture content, drug content and in-vitro drug release. The results concluded that the formulation F2 (with HPMC and EC in 2:1 ratio) showed 80.89% in drug release during in-vitro studies after 24 hours. With the incorporation of PEG-400 and DMSO smooth, transparent and flexible film were produced.